Modern models of managing quality of educational services in universities - Jumasheva, S.M. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the three main groups of quality models, which form the basis of the quality assurance system in higher educational institutions. The following models are considered in more details: model of the European Foundation for Quality Management (EFQM); model operating on the principles of the Total Quality Management (TQM), meeting the requirements of ISO 9000; ENQA model (European Association for Quality Assurance in Higher Education), aligned with the «The Standards and Guidelines for Quality Assurance in the European Higher Education Area» (ESG). Measures taken to ensure the quality of higher education in universities are considered. Positive trends in the sphere of ensuring quality of education were noted. Also, the main problems in the creation and functioning of quality management systems in universities were revealed. One of the solutions to these problems is the use of modern information technologies. It is noted that some universities continue to use outdated principles of quality management of higher education. Not all universities are guided by the mission, vision, strategic plan in the construction of quality education systems. In most of the universities only knowledge of students is assessed, assessment of skills and competencies is not carried out. Upon analysis, recommendations for the effective functioning of quality assurance systems in higher education institutions were made.